Optimization of a mouse immunization protocol with Paracoccidioides brasiliensis antigens - Almeida, Armando Vieira [UNESP]; Fogaça, Joel [UNESP]; Chamma, Luiz Gastão [UNESP]; Fecchio, Denise [UNESP]; Franco, Marcello [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1995)
The objectives of the present study were to optimize the protocol of mouse immunization with Paracoccidioides brasiliensis antigens (Rifkind's protocol) and to test the modulation effect of cyclophosphamide (Cy) on the delayed hypersensitivity response (DHR) of immunized animals. Experiments were carried out using one to four immunizing doses of either crude particulate P. brasiliensis antigen or yeast-cell antigen, followed by DHR test four or seven days after the last immunizing dose. The data demonstrated that an immunizing dose already elicited response; higher DHR indices were obtained with two or three immunizing doses; there were no differences between DHR indices of animals challenged four or seven days after the last dose. Overall the inoculation of two or three doses of the yeast-cell antigen, which is easier to prepare, and DHR test at day 4 simplify the original Rifkind's immunization protocol and shorten the duration of the experiments. The modulation effect of Cy on DHR was assayed with administration of 2.5, 20 and 100 mg/kg weight at seven day intervals starting from day 4 prior to the first immunizing dose. Only the treatment with 2.5 mg Cy increased the DHR indices. Treatment with 100 mg Cy inhibited the DHR, whereas 20 mg Cy did not affect the DHR indices. Results suggest an immunostimulating effect of low dose of Cy on the DHR of mice immunized with P. brasiliensis antigens.
Keywords: Paracoccidioides brasiliensis; immunization; paracoccidioidomycosis